Optimization of the Synthesis of Superhydrophobic Carbon Nanomaterials by Chemical Vapor Deposition - Aljumaily, Mustafa Mohammed; AlSaadi, Mohammed Abdulhakim; Das, Rasel; Hamid, Sharifah Bee Abd; Hashim, Nur Awanis; AlOmar, Mohamed Khalid; Alayan, Haiyam Mohammed; Novikov, Mikhail; Alsalhy, Qusay F.; Hashim, Mohd Ali (Nature Research, 2018)
Demand is increasing for superhydrophobic materials in many applications, such as membrane distillation, separation and special coating technologies. In this study, we report a chemical vapor deposition (CVD) process to fabricate superhydrophobic carbon nanomaterials (CNM) on nickel (Ni)-doped powder activated carbon (PAC). The reaction temperature, reaction time and H2/C2H2 gas ratio were optimized to achieve the optimum contact angle (CA) and carbon yield (CY). For the highest CY (380%) and CA (177°), the optimal reaction temperatures were 702 °C and 687 °C, respectively. However, both the reaction time (40 min) and gas ratio (1.0) were found to have similar effects on CY and CA. Based on the Field emission scanning electron microscopy and transmission electron microscopy images, the CNM could be categorized into two main groups: A) carbon spheres (CS) free carbon nanofibers (CNFs) and b) CS mixed with CNFs, which were formed at 650 and 750 °C, respectively. Raman spectroscopy and thermogravimetric analysis also support this finding. The hydrophobicity of the CNM, expressed by the CA, follows the trend of CS-mixed CNFs (CA: 177°) CSfree CNFs (CA: 167°) PAC/Ni (CA: 65°). This paves the way for future applications of synthesized CNM to fabricate water-repellent industrial-grade technologies.